Single or Multiple Organizational Identities: The Management Consultant’s Dilemma - Chelliah, J.; D'Netto, Brian; Georges, S. (Tennessee State University College of Business, 2015)
In this article, we examine the signals consulting firms send to clients and the public through the identities they publish on their websites. The paper begins with a review of academic and practitioner literature on consulting identities and typologies. The literature review leads us to conclude that the consultant cannot be conceptualized by a single definable construct but rather by multiple typologies. To demonstrate this we establish a theoretically informed framework summarizing the main consulting identities from extant literature. The framework is then applied to a sample of 50 consulting organizations currently operating in Australia. Through the application of this framework, the identity of the consulting firms are seen to be multiple and sometimes contradictory in nature. Finally, we discuss the possible strategic implications of identity multiplicity, correlating identity with legitimacy and impression management techniques.